Nasopharyngeal airway and subcranial space analysis in Pfeiffer syndrome. Issue 5 (June 2021) - Lu, X.; Forte, A.J.; Allam, O.; Park, K.E.; Junn, A.; Alperovich, M.; Steinbacher, D.M.; Tonello, C.; Alonso, N.; Persing, J.A.
Abstract: Tracheotomy in infancy helps patients with Pfeiffer syndrome to survive by preventing respiratory crisis, but difficulty in decannulation may consequently be a challenge. This study has investigated the regional abnormalities of the nasopharyngeal airway in children with Pfeiffer syndrome to provide an anatomical basis for the surgical treatment and decannulation of the upper airway. Seventy-two preoperative computed tomograms (CT) (Pfeiffer syndrome n=30; control n=42) were included. The airway volume, cross-sectional area, and cephalometrics were measured using Materialise software. Patients with Pfeiffer syndrome developed a 50% (p<0.001) reduction of nasal airway volume, and a 44% (p=0.003) restriction in pharyngeal airway volume. In patients with Pfeiffer syndrome the cross-sectional area at the choana was only half that of the controls (p<0.001). The posterior width of the nasal airway in patients with Pfeiffer syndrome was shortened by 13% (p=0.003), and the height reduced by 21% (p<0.001). The cross-sectional areas at the condylion and gonion levels, which indicate the calibre of the pharyngeal airway at the entrance and midsection, were reduced by 67% (p<0.001) and 47% (p<0.001), respectively, when compared with the controls. The volume of the nasal airway in patients with Pfeiffer syndrome was significantly restricted in length, height, and width, and by choanal stenosis in all cases in this cohort. The reduced anteroposterior length of the nasal airway contributed to the shortened maxilla more than the anteroposterior position. The limited height and width of the nasal pathway was the result of a hypoplastic sphenoid. Restricted mediolateral and anteroposterior dimensions were evident across the entire course of the pharyngeal airway. Mediolateral maxillary expansion in addition to maxillomandibular advancement is therefore likely to benefit these patients.